Sibling Relationships Over the Life Course: Growing Up With a Disability. (October 2019) - Avieli, Hila; Band-Winterstein, Tova; Araten Bergman, Tal
The research explores sibling relationships, and the ways in which they are shaped over the life course by family members, in families with a lifelong disability. In-depth, semistructured interviews were conducted with 15 family units including a parent, a sibling, and an adult sibling with a disability. The content analysis revealed five sibling relationship patterns: (a) "Not a child, but a parent caretaker"—the parent–surrogate sibling; (b) "We somehow grew apart"—the estranged sibling; (c) "It is important for me to maintain some kind of distance"—the bystander sibling; (d) "When there's something they want to tell him, they always send me"—the mediator sibling; and (e) "I love him to death"—the friend sibling. These patterns of adult sibling relationships are discussed in relation to family dynamics, values, and legacies; recommendations for practice and research are made.